Pengaruh Penambahan Berbagai Variasi CoatingTerhadap Karakteristik MutuFilletIkan Kakap Putih (Lates Calcarifer Sp) selama Penyimpanan Dingin - I Wayan Widia; I Putu Yosan Budana; Ida Bagus Putu Gunadnya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
White snapper ( Lates calcarifer sp ) is a perishable fishery product, so it needs to be handled properly during storage. Using chitosan and ci n namon essential oil as a coating has the potential to be used as an antibacterial. The purpose of this study was to determine the effect of adding various coating variations and the best coating treatment on the quality characteristics of barramundi fillet s during storage. This study used CRD (completely randomized design). The coating addition treatment consists of no coating, coating with the addition of 1.5g chitosan, coating with the addition of 1.5% cinnamon essential oil and coating with a combination of 1.5g chitosan and 1.5% cinnamon essential oil, with repetition twice and the sample will be stored at temperature. 15 o C for 8 days. The research results showed that the addition of 1.5g chitosan and 1.5% cinnamon essential oil as well as a combination treatment with 1.5g chitosan and 1.5% cinnamon essential oil as a coating provided different effects during cold storage in terms of the parameters pH, pH, texture (hardness), color difference, TVB and TPC. The best treatment was found in coating using cin n amon essential oil 1.5% during cold storage until day 8 with a pH value of 5.9, texture (hardness) 3.1476 N, color difference 7.6, total volatile base 44.70 mg N /100 g, total plate count 5.79 CFU/g.